Case report: Rare novel MIPEP compound heterozygous variants presenting with hypertrophic cardiomyopathy, severe lactic acidosis and hypotonia in a Chinese infant - Wang, Ling; Lu, Pengtao; Yin, Jie; Xu, Kangkang; Xiang, Dandan; Zhang, Zhongman; Zhang, Han; Zheng, Bixia; Zhou, Wei; Wang, Chunli; Yang, Shiwei (Frontiers in Cardiovascular Medicine, 2023)
Mitochondrial intermediate peptidase (MIP), encoded by the MIPEP gene, involving in the maturation of oxidative phosphorylation-related proteins. Combined oxidative phosphorylation deficiency-31 (COXPD31) (OMIM: 617228) is a rare autosomal recessive multisystemic disorder, characterized by infantile onset of left ventricular noncompaction, hypertrophic cardiomyopathy (HCM), dilated cardiomyopathy, global developmental delay, and severe hypotonia associated with MIP deficiency in the heart, brain, and skeletal muscles. Here we first reported a rare case of an 8-month-old boy in China with MIPEP variations who presented with HCM, severe lactic acidosis, and hypotonia. Genetic analysis revealed novel compound heterozygous variants c.1081T>A (p. (Tyr361Asn)) and the whole gene deletion (Ex1_19 del) in the MIPEP gene. Our findings further expand the clinical and genetic spectrum of COXPD31, and highlight the importance of an interrelationship between clinical and research efforts for disease gene identification.